Identification of Students’ Conception Profile on Chemical Equilibrium Material Using 4TMC Diagnostic Test Instrument - Novita, Dian; Rachmadhaniar, Reta Nareswari (FKIP Universitas Lampung, 2024)
Abstract: Identification of Students' Conception Profile on Chemical Equilibrium Material Using 4TMC Diagnostic Test Instrument. Objectives: This study aims to identify students' conceptions of chemical equilibrium material using the 4TMC diagnostic test instrument. Methods: Pre-experimental research with a one-shot case study design by giving treatment to a group of students and then observing the results obtained. Findings: Some students still experience conceptual errors in chemical equilibrium material. In the concentration factor, students were identified as understanding the concept by 15.3%, not understanding the concept by 43.3%, and misconceptions by 41.4%. In the pressure and volume factors, students were identified as understanding the concept by 16.7%, not understanding the concept by 52%, and misconceptions by 31.3%. In the temperature factor, learners were identified as understanding the concept by 22.7%, not understanding the concept by 48.7%, and misconceptions by 28.6%. Conclusion: Based on the results and discussion of the research, it can be concluded that the development of the 4TMC diagnostic test instrument developed can identify the conceptions of students on chemical equilibrium material. Diagnostic test instruments are important to use as an evaluation material of the learning process carried out by the teacher. Keywords: identification, conception profile, 4TMC diagnostic test.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202439